Milk quality analysis in Southwestern Uganda - Rutaro, Hamid (Kansas State University, 2015)
As the dairy industry faces the future, consumers’ demand for better milk quality and safety is increasing. Milk quality is of major interest to both consumers and dairy farmers alike. However, scientific data on milk quality in terms of somatic cell count (SCC) in Uganda and most developing countries has been lacking. This study used SCC to compare Southwestern Uganda’s milk quality against international standards. The study also sought to assess dairy farmers’ perceptions about milk quality. Milk samples were obtained from 100 farms in Mbarara and Kiruhura districts, the major cattle corridor in Uganda. The milk’s SCC was analyzed using a DeLaval DCC. A structured questionnaire surveyed farmers on milking procedures and milk-quality perception. Descriptive statistics and qualitative analysis was used to characterize and compare milk quality against the international benchmark. The study found that the 100 farms had an average SCC of 507,000 cells/ml. About 34% of farms in the study had SCC under 200,000 cells/ml, an indication of high-quality milk. Excluding 7% of the farms with SCC over 1,000,000 cells/ml, the remaining 93% had an average SCC of 276,000 cells/ml, a level comparable to international standards, well below the EU threshold of 400,000. The study also revealed that 98% of farmers considered milk quality as important or very important both to them and to the milk buyers. However, all farmers reported that they currently do not receive a milk-quality premium and are not penalized for poor quality. Seventy-nine percent of farmers reported the cooperative they belong to as their main source of information on management practices. An improved perception of milk quality both domestically and internationally will benefit Uganda’s dairy farmers and its dairy industry at large. Consumers must be assured that Uganda’s dairy industry, its government, industry stakeholders such as the Dairy Development Authority, the Uganda National Bureau of Standards, and the private sector place the utmost importance on the quality and safety of milk and other dairy products. New technologies to measure for SCC and strict food safety regulations will help improve the country’s milk-quality image, allowing Uganda’s dairy industry to tap into major milk export markets. Most developed countries have seen increased raw-milk quality or reduced SCC as a result of strong regulatory pressure.
Keywords: Milk; Milk Quality; Somatic Cell Count; Smallholder Dairies; Uganda; Dairy Industry; Agriculture, General (0473); Economics, Agricultural (0503)